Comparative growth performance of crossbred calves fed on complete diet in mash or block form - Singh, K K; Das, M M; Samanta, A K; Kundu, S S (The Indian Journal of Animal Sciences, 2007)
Effect of different forms of complete diet (roughage: concentrate: : 60: 40) on rumen ecosystem vis-a-vis nutrient utilization in growing crossbred calves was studied. Crossbred female calves (12), 10-12 months old, average body weight 89.25±5.40 kg were randomly divided into 2 groups of 6 each. The diet containing grass hay and concentrate mixture was fed to group T1 in mash form and block form to group T2. Higher DM intake (2.69 vs 2.18 kg% of body weight), anaerobic bacteria, fungal population and lower (P&lt 0.05) protozoal population and ruminal ammonia-N concentration was observed in group T2 than that in group T1. However, digestibility of nutrients between the treatment groups was not significant. As a result, growth performance of calves was higher in group T2 than in group T1. Therefore, it is concluded that the complete diet in block form enhanced the dry matter intake by 30% and average daily gain by 35% in female crossbred calves.